The Influence of a Pectinase and Pectinase/hemicellulases Enzyme Preparations On percentage Pineapple Juice Recovery, Particulates and Sensory Attributes - Tochi, Bitange Nipa; Wang, Zhang; Xu, Shi-Ying; Zhang, Wenbin (Pakistan Journal of Nutrition, 2009)
Two commercial enzyme preparations (from Aspergillus niger), a pectinase and a liquid pectinase/hemicellulases were used singly or in combination at a rate 0.03% (w/w) in a two step extraction of pineapple juice at 35, 37.5 and 40oC for 30 min. The percentage juice recovery, soluble sugars, total phenolics, titratable acidity, viscosity and turbidity of the recovered juice were measured to ascertain the influence of the enzyme preparations on extraction against the control. The ready to serve pineapple juice (RTS) was rated for acceptance on a 5 point hedonic scale.